2016
DOI: 10.1016/j.ihj.2015.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic parameters in clinical responders to surgical pericardiectomy – A single center experience with chronic constrictive pericarditis

Abstract: Among clinical responders to surgical pericardiectomy, echocardiographic assessment revealed a significant reduction in vena caval congestion, LA size, ratio of LA to aortic annulus, septal bounce, respiratory variation in mitral and tricuspid E velocities, mitral annular medial e' and the phenomenon of annulus reversus. Also, there was a significant rise in minimum tricuspid and mitral E velocities and the E/e' ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The various echocardiographic parameters such as IVC congestion, mean LA size, mitral and tricuspid E velocity and TDI findings significantly improved in a study from central India comprising 23 patients of post-pericardiectomy. 17 In our study, there was significant respiro-phasic variation in the mitral and tricuspid E velocity in all patients ( P < 0.001). Tissue Doppler imaging (TDI) is a useful for distinguishing CCP from restrictive cardiomyopathy.…”
Section: Discussionsupporting
confidence: 51%
“…The various echocardiographic parameters such as IVC congestion, mean LA size, mitral and tricuspid E velocity and TDI findings significantly improved in a study from central India comprising 23 patients of post-pericardiectomy. 17 In our study, there was significant respiro-phasic variation in the mitral and tricuspid E velocity in all patients ( P < 0.001). Tissue Doppler imaging (TDI) is a useful for distinguishing CCP from restrictive cardiomyopathy.…”
Section: Discussionsupporting
confidence: 51%
“…The lateral e' did not change significantly before and after the operation, but the septal e' decreased after the operation. According to a report by Patil et al, post-operative septal bounce and respiratory variation in mitral and tricuspid E velocities are significantly improved, along with a decrease in septal e', resulting in improvement of "annulus reversus" [9]. These findings were also recognized in our case and are considered important evaluation factors for predicting post-operative prognosis.…”
Section: Discussionsupporting
confidence: 74%
“…Regarding the evolution of echocardiographic signs during the first post-operative year, the disappearance of constriction was noted in all patients (100%). A recent study [ 50 ] comparing the preoperative and postoperative echocardiography demonstrated a significant reduction in the congestion of the inferior vena cava from 100% to 15% of cases, a reduction in the size of the left atrium from 39.33±10.52 mm to 34.45±10.08 mm, a reduction in the paradoxical septum and respiratory variations in mitral inflow velocity. In our patients with preoperative RV dysfunction, improvement in RV function was noted in a single patient within 14 months.…”
Section: Discussionmentioning
confidence: 99%